Proteomic bronchiolitis obliterans syndrome risk monitoring in lung transplant recipients - Wolf, Thomas; Oumeraci, Tonio; Gottlieb, Jens; Pich, Andreas; Brors, Benedikt; Eils, Roland; Haverich, Axel; Schlegelberger, Brigitte; Welte, Tobias; Zapatka, Marc; von Neuhoff, Nils (Transplantation, 2011)
Background: Obliterative bronchiolitis poses a primary obstacle for long-term survival of lung transplant recipients and manifests clinically as bronchiolitis obliterans syndrome (BOS). Establishing a molecular level screening method to detect BOS-related proteome changes before its diagnosis by forced expiratory volume surrogate marker criteria was the main objective of this study. - Methods: Bronchoalveolar lavage was performed in 82 lung transplant recipients (48/34 with/without known BOS development) at different time points between 12 and 48 months after lung transplantation. A mass spectrometry-based method was devised to generate bronchoalveolar lavage fluid proteome profiles that were screened for BOS-specific alterations. Statistically significant marker peptides and proteins were identified and validated by in-gel digestion, tandem mass spectrometric sequencing, and quantitative immunoassays. - Results: Among the panel of statistically significant markers were Clara cell protein, calgranulin A, human neutrophil peptides, and the antimicrobial agent histatin. To assess their clinical relevance, a highly sensitive and specific classifier model was developed. Positive BOS classification by monitoring of seven polypeptides correlated strongly with a significant decrease in BOS-free time. Thus, it was possible to detect high-risk patients early on in the pathogenetic process. - Conclusions: Monitoring the bronchoalveolar lavage fluid levels of seven polypeptides detected by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry allows a reliable prediction of early BOS using a Random Forest decision tree-based classifier model. The high accuracy of this robust model and its synergistic potential in combination with established forced expiratory volume-based diagnostics could make it an effective tool to supplement the current diagnostic regime after multicentric validation.
Gesehen am 24.11.2022